PERUBAHAN SIFAT FISIK SAMPAH ORGANIK PADAT PADA PROSES PENGOMPOSAN SECARA OPEN WINDROW DI BIOREAKTOR TIPE SETENGAH SILINDER - Setiyo, Yohanes (Agrotekno; Vol 13, No.2 Agustus 2007)
This research was to identification physical properties change along organic municipal solid waste composting. Bulk density, moisture content, particle size of compost, and porosity were observed every one week at three point deep of composting process. Oxygen concentration at the critical point was observed for cheking the diffusion potential of air, observation of it was everyday by cosmotector tipe XPO-317. Relation equation between bulk density, porosity and moisture content with time of composting were described by ? = -0.0966 t2 + 9.23 t + 147.8 with value of was r2 = 0.95, ? = - 0.0292Ln(t) + 0.745 with value of was r2 = 0.944, and Mc = - 0.0785Ln(t) + 0.8685 with value of was r2 = 0.95. Process should be futher supported with a turning over of the compost done weekly so the availability of O2 at 50 to 190 g kg-1 air.
Keywords: physical properties, composting,open windrow